Exploring Students’ Needs in Digipreneurship: A Preliminary Study for Developing A Content-Based Business Worksheet - Muhammad Akbar Budiman; Annisa Oktavia Lestari; Beny Dwi Saputra (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
The rapid growth of the digital economy has amplified the potential of Generation Z to engage in content-based entrepreneurship. However, the lack of instructional materials that specifically address their learning needs creates a gap that hinders the development of their digital entrepreneurial competencies. This study aims to analyze students’ target and learning needs as a preliminary stage in developing a Content-Based Business Worksheet using a Project-Based Learning approach. The research involved 92 students from the Economic Education program as participants. The data were collected through an online questionnaire consisting of 20 items, covering two dimensions: target needs and learning needs. The instrument was validated by experts and tested for reliability, yielding a Cronbach’s Alpha coefficient of 0.87, indicating high internal consistency. The data were analyzed descriptively using mean scores supported by a deeper examination of response patterns, priority rankings, and thematic interpretation of students’ target and learning needs. The results show that students have a very high need for understanding digipreneurship concepts, content creation strategies, and monetization techniques in digital business. They also express strong preferences for flexible learning, structured guidance, collaborative project work, and continuous feedback in the learning process. These findings highlight the importance of developing a structured and innovative learning worksheet that integrates digital tools and project-based activities to foster creativity, collaboration, and entrepreneurial intention among students. This study suggest the worksheet developed can enhance students’ digital entrepreneurial competence and motivation to become a content creator.Keywords: Digipreneurship, content-based business, project-based learning, needs analysis, digital entrepreneurship